Improvement of thermophysical quality of biomass pellets produced from rice husks. (December 2021) - Djomdi,; Fadimatou, H.; Hamadou, B.; Nguela, L.J. Mintsop; Christophe, G.; Michaud, P.
Abstract: This work was initiated to improve the thermophysical quality of biomass pellets produced from rice husks using arabic gum. Dried and crushed arabic gum was solubilized in a 1:2, 1:3 and 1:4 m/v binder/water ratios. In addition, the rice husks and pellets were physiochemically characterized. The formulation of the mixture was carried out by mixing rice husks of diameter less than or equal to 0.5 mm with arabic gum. It emerges from this work that the rice husks from the SEMRY (Yagoua Rice Expansion and Modernization Company) from Yagoua in the Far North Region of Cameroon, had 94.736, 17.046, 67.454, and 15.5% dry matter, ash, organic matter and fixed carbon respectively. Their Lower Heating Value (LHV) and electrical conductivity were 1178 J/g and 0.756 mS/cm respectively. The solid biofuel (pellets) obtained show a water content varying between 7.97 and 9.794%. Their shock resistance, friability index and Lower Heating Value (LHV) depend on the concentration of the binder used. The thermophysical characteristics of biomass pellets were proportional to the volume of binder and compaction. The 1:2 binder/water ratio showed the best thermophysical characteristics.